2009
DOI: 10.1136/thx.2008.099143
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic challenge flight assessments in patients with severe chest wall deformity or neuromuscular disease at risk for nocturnal hypoventilation

Abstract: Background: The British Thoracic Society (BTS) recommendations for patients with respiratory disease planning air travel suggest that an oxygen saturation (SaO 2 ) .95% precludes the need for any further assessment of the need for supplemental oxygen during flight. A hypoxic challenge test (HCT) is recommended for patients with a resting SaO 2 between 92% and 95% with an additional risk factor, including kyphoscoliosis (KS) or neuromuscular disease (NMD). However, this recommendation was based on very few data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 7 publications
1
29
0
1
Order By: Relevance
“…A recent study205 examined 21 patients (16 with idiopathic kyphoscoliosis and five with neuromuscular disease). Thirteen were male and the median age was 58 years (range 22–73).…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…A recent study205 examined 21 patients (16 with idiopathic kyphoscoliosis and five with neuromuscular disease). Thirteen were male and the median age was 58 years (range 22–73).…”
Section: Background Literature Reviewmentioning
confidence: 99%
“…We read with great interest the paper by Mestry et al 1 which analysed hypoxic challenge flight assessments in patients with restrictive disorders. In their study they dispute the current British Thoracic Society recommendations, demonstrating that, in this subgroup, all patients planning air travel should have a pre-flight evaluation because, even in patients with normal baseline oxygen saturation (Sa o 2 ), arterial oxygen tension (Pa o 2 ) can fall below 6.6 kPa during hypoxic challenge.…”
mentioning
confidence: 99%
“…According to the Aerospace Medical Association guideline published in 2003, baseline PaO 2 is considered the best predictor of altitude PaO 2 , but our data do not support this observation. Several previous studies in both obstructive and non‐obstructive lung diseases have also shown that baseline PaO 2 does not reliably predict the degree of desaturation during HCT …”
Section: Discussionmentioning
confidence: 95%